MCT8 is Downregulated by Short Time Iodine Overload in the Thyroid Gland of Rats - de Souza, E. C. L.; Dias, G. R. M.; Cardoso, R. C.; Lima, L. P.; Fortunato, R. S.; Visser, T. J.; Vaisman, M.; Ferreira, A. C. F.; Carvalho, D. P. (Hormone and Metabolic Research, 2015)
Wolff-Chaikoff effect is characterized by the blockade of thyroid hormone synthesis and secretion due to iodine overload. However, the regulation of monocarboxylate transporter 8 during Wolff-Chaikoff effect and its possible role in the rapid reduction of T4 secretion by the thyroid gland remains unclear. Patients with monocarboxylate transporter 8 gene loss-of-function mutations and monocarboxylate transporter 8 knockout mice were shown to have decreased serum T4 levels, indicating that monocarboxylate transporter 8 could be involved in the secretion of thyroid hormones from the thyroid gland. Herein, we aimed to evaluate the regulation of monocarboxylate transporter 8 during the Wolff-Chaikoff effect and the escape from iodine overload, besides the importance of iodine organification for this regulation. Monocarboxylate transporter 8 mRNA and protein levels significantly decreased after 1 day of NaI administration to rats, together with decreased serum T4; while no alteration was observed in LAT2 expression. Moreover, both monocarboxylate transporter 8 expression and serum T4 was restored after 6 days of NaI. The inhibition of thyroperoxidase activity by methimazole prevented the inhibitory effect of NaI on thyroid monocarboxylate transporter 8 expression, suggesting that an active thyroperoxidase is necessary for MCT8 downregulation by iodine overload, similarly to other thyroid markers, such as sodium iodide symporter. Therefore, we conclude that thyroid monocarboxylate transporter 8 expression is downregulated during iodine overload and that the normalization of its expression parallels the escape phenomenon. These data suggest a possible role for monocarboxylate transporter 8 in the changes of thyroid hormones secretion during the Wolff-Chaikoff effect and escape.
Keywords: monocarboxylate transporter 8; Wolff-Chaikoff effect; thyroid hormone transporter; iodide; iodo compounds; escape